Association Between Familial Mediterranean Fever and Cachexia in Females - Yunus DURMAZ,; İlker İLHANLI,; Ahmet Kıvanç CENGİZ,; Ece KAPTANOĞLU,; Zekiye ÖZKAN HASBEK,; Sami HİZMETLİ, (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the association between familial Mediterranean fever (FMF) and cachexia in females. Patients and methods: The study included 32 female FMF patients (median age 27.50 years; range, 18 to 50 years) and 30 female healthy controls (median age 32 years; range, 18 to 50 years). Patients were classified according to Tel-Hashomer criteria. Circumference of arm, waist, and thigh was recorded. Short form 36 (SF-36) and Multidimensional Assessment of Fatigue (MAF) scale were applied. Composition of the body was measured with dual X-ray absorption. Muscle strength was measured with an isokinetic dynamometer, and strength of hand grip was measured from dominant hand with a hand dynamometer. C-reactive protein, erythrocyte sedimentation rate, fibrinogen and serum creatinine kinase (CK) levels were recorded. Results: Body mass index was significantly higher in controls. Twelve patients and one control had cachexia. CK level was significantly higher in patients than controls. Mass of muscle without fat was significantly higher in patients than controls. Peak torque values of extension and flexion at the velocity of 60°/second [Newton meter (Nm)], and value of total work during extension at the velocity of 240°/second (Nm) in isokinetic measures were significantly higher in controls. MAF score was significantly higher in patients with cachexia than patients without cachexia where the subscale scores of SF-36, except the vitality score, were significantly lower in patients with cachexia. However, Tel-Hashomer score was significantly higher in patients with cachexia. Conclusion: This study pointed at a significant association between cachexia and FMF in females. Muscle endurance was not affected in FMF patients with cachexia; however, decreased muscle strength, impaired quality of life and increased fatigue were observed in these patients.